Caracterização de genótipos de milho para produção de silagem - Vieira, Valmir da Cunha (2011)
The aim of this work was to evaluate the phytotechnical and bromatological characteristics of corn (maize) genotypes for silage production, and to verify whether the different genetic bases (single, three-way, double and inter-varietal hybrids and cultivated varieties) and grain texture (hard, semi-hard and dent) affect genotype suitability for silage production. The experiment was carried out in the experimental area of Paraná Federal Technology University (UTFPR) at the Dois Vizinhos Campus between October 2009 and March 2010. The trial cultivars evaluated were: “Centro superprecoce” [Central Super Early] (32 genotypes), “Sul superprecoce” [South Super Early] (30 genotypes) and “Sul precoce normal” [Central Normal Early] (36 genotypes) from the Rede Nacional de Genótipos de Milho [National Network of Corn Genotypes], provided by Embrapa Milho e Sorgo (Sete Lagoas, MG). The experimental arrangement was a randomized blocks design with two replications and the phytomorphological and bromatological characters of the corn crop were evaluated. In each trial, genotypes were grouped according to their genetic bases and then on the basis of grain texture, using the Scheffée method, and next, a Scott-Knott test was run. Results showed that neither the genetic base nor the grain texture affected genotype suitability. However, taken individually, some of the genotypes could be recommended for corn silage production.